PAI Learning Model Based on NeNeMo Principles, Simple, Equal, and Sustainable in the Implementation of Islamic Character Education in Tulang Bawang Barat District Elementary Schools - Afif Alfiyanto; Azhar Azhar; M. Ikhwan; Dedi Wahyudi (Edumaspul: Jurnal Pendidikan, 2023)
This study aimed to determine the PAI learning model based on NeNeMo, Simple, Equal, and Sustainable principles in implementing Islamic character education in Tulang Bawang Barat District Elementary School. The research method uses the literature review method. The results showed that 1) the District Government, to accelerate the quality and progress of non-material education, uses the principles of Nenemo (Nemen, Nedes, Nerimo), simple, equal, and sustainable (abbreviated as 3NSSL), which is then compiled into character education modules; 2) Islamic character education through the Nenemo-SSL principle aims to a) prepare students as prospective leaders of the nation and successors of regional leaders with noble characters and values owned by the Indonesian nation and especially West Tulang Bawang Regency; b) Prepare students to face the challenges of rapid globalization and rapid technological growth; 3) Islamic character education through the Nenemo-SSL principle is applied to elementary schools at the same level (SD / MI), junior high schools at the same level (SMP / MTs), and high schools at the same level (SMA / SMK / MA)